Intergroup Relations among Ethnically Diverse University Students in Ethiopia - Adamu, Abebaw Yirga (Journal of Education and Research, 2013)
This study focused on examining the intergroup relations among ethnically diverse university students. The study was conducted in Bahir Dar University, one of the public universities in Ethiopia– a country of “indigenous ethnic diversity”. The participants were students, teachersand support staff selected usingpurposive and snowball sampling.The necessary data were collected throughinterview andfocus group discussion. The studyrevealed different factors that are internal and external to the university facilitateand impede intergroup relations among students. The study also showed that students generally have positive attitude toward outgroups and developing positive intergroup relations. This finding has very strong implications in managing intergroup relations not only in universities but also in the society. The university management, however, was found unable to provide much support to such positive attitudesand promoting diversity mainly because of lack of institutional priority as well as managers’ confidence and diversity management skills. DOI: http://dx.doi.org/10.3126/jer.v3i2.8399 Journal of Education and Research August 2013, Vol. 3, No. 2, pp. 77-95